الخصائص النفسية والاجتماعية لمدمن المخدرات: الخصائص النفسية والاجتماعية لمدمن المخدرات (Elmergib Journal of Human Sciences, 2025)
This study aims to examine the psychological and social characteristics of drug addicts, and to identify the major consequences of drug abuse across different dimensions—psychological, social, health-related, legal, and religious. The research relied on a review of relevant literature and previous studies, in addition to analyzing the findings within the theoretical framework.The results revealed that drug abuse leads to various psychological disorders, including anxiety, tension, depression, poor concentration, and diminished cognitive abilities, alongside physical complications such as fatigue, headaches, and tremors. Furthermore, addicts display negative social characteristics, most notably family disintegration, weakened social relationships, frequent conflicts, and engagement in deviant environments, all of which contribute to a gradual deterioration of personal and social traits.At the international level, the study highlighted that global and Arab organizations have devoted significant attention to combating drugs, through the establishment of specialized offices, the enactment of deterrent legislation, and the organization of international conferences. The World Health Organization has also emphasized that addiction constitutes both a psychological and physiological condition requiring preventive and therapeutic interventions.The study concludes that addressing drug abuse necessitates an integrated approach combining preventive, therapeutic, and legislative measures, while reinforcing the role of families, educational, religious, and health institutions, as well as civil society, in curbing this phenomenon. It further recommends conducting in-depth field studies, organizing awareness campaigns, and expanding rehabilitation centers, in order to reintegrate addicts into society in a healthy and constructive manner.